Reconstruction of an Amputated Thumb by Great Toe Harvested from a Simultaneously Amputated Lower Limb: “Spare Part Surgery” Concept Revisited - Sabapathy, S Raja; Venkatramani, Hari; Periasamy, Madhu; Narasimhan, Aditya; Mohan, Monusha; Muthukumar, Vamseedharan (Indian Journal of Plastic Surgery, 2025)
Utilization of tissues from the amputated part to cover critical structures or enhance function in another area is a valuable technique in reconstructive surgery. For this “spare part surgery” to occur high level of awareness is to be present among surgeons who perform the primary procedure. We are presenting a case wherein the great toe was harvested for thumb reconstruction in a patient who had a nonsalvageable lower limb injury with a crush injury of the hand with amputation of multiple fingers including the thumb. The patient on follow-up is using his reconstructed thumb for all his activities including for wearing the lower limb prosthesis. Harvesting the toe from the to be amputated part has the advantages of harvesting more skin, longer length of tendons, vessels, and nerves since there is no need for donor site closure or any concern for donor site morbidity.
Keywords: toe transfer; thumb reconstruction; spare part surgery